Dissolution rate limited bioavailability of flutamide, and in vitro – in vivo correlation - Posti, Juhani; Katila, Kirsi; Kostiainen, Timo (European journal of pharmaceutics and biopharmaceutics, 2000)
Flutamide is due to its properties as a practically water-insoluble, high-dose drug substance a typical representative of a drug with particle size limited dissolution rate and bioavailability. An in vitro dissolution test method comprising of standard paddle stirrer, round-bottomed vessel of 4 l capacity, and 0.1 N hydrochloric acid with 0.5% of sodium lauryl sulphate as dissolution medium, was developed. The dissolution method was shown discriminatory and predictive regarding bioavailability of conventional 250 mg flutamide tablets with different in vitro dissolution rates. Relative bioavailability of flutamide from the tablets, determined as AUC of the active metabolite 2-hydroxyflutamide in healthy male subjects, could be correlated with drug amount dissolved during 45 min in the in vitro test. Also bioavailability data from four different biostudies could be compared utilising the calculated ratios R AUC and R Diss. for the test and reference formulations in the individual studies. It is suggested that the concept of R AUC and R Diss. can also be applied to other orally administered, poorly soluble, high-dose drug substances with dissolution rate limited bioavailability.